Detection of landscape species as a low-cost biomonitoring study: Cr, Mn, and Zn pollution in an urban air quality - Yayla, Emine Emel; Sevik, Hakan; Isinkaralar, Kaan (Springer Science and Business Media LLC, 2022)
Urban air pollution in cities, among the world's most critical problems, has escalated to such an extent that it threatens human health in many urban centers and causes the death of millions every year. Trace metals are significant among the components of air pollution. Trace metals can endure long without undergoing biodegradation and bioaccumulation in living organisms. Moreover, their concentration in the air increases gradually. Therefore, monitoring metal concentration is extremely important for reliable indicators of environmental pollution. Biomonitoring is an effective method for describing metal concentrations in urban areas. Chromium, manganese, and zinc, selected within the present study, have various adverse effects on plants in high concentrations. Their identification is highly critical for monitoring the pollution level in their regions. This study aimed to determine the Cr, Mn, and Zn concentration changes according to organ, and age in Elaeagnus angustifolia L., Platanus orientalis L., Koelreuteria paniculata Laxm, Ailanthus altissima (Mill.) Swingle, and Cedrus atlantica (Endl.) Manetti ex Carr is 30 years old. The accumulation of metals in the outer bark can be found as follows Zn > Mn > Cr in all species, although Ailanthus altissima (Mill.) Swingle and Platanus orientalis L. can be suitable for biomonitoring tools because concentrations change significantly depending on the airborne metal.
Keywords: Adult; Air Pollutants; Trace Elements; Zinc; Metals; Air Pollution; Metals, Heavy; Humans; Biological Monitoring; Environmental Monitoring; 15. Life on land; 3. Good health; 13. Climate action; 11. Sustainability